2022
DOI: 10.1021/jacs.2c04734
|View full text |Cite
|
Sign up to set email alerts
|

Sheet-like 2D Manganese(IV) Complex with High Photothermal Conversion Efficiency

Abstract: We report a stable, water-soluble, mononuclear manganese­(IV) complex [MnIV(H2 L)]·5H2O (Mn-HDCL) that acts as an efficient photothermal material. This system is based on a hexahydrazide clathrochelate ligand (L/HDCL) and is obtained via an efficient one-pot templated synthesis that avoids the need for harsh reaction conditions. Scanning tunneling microscopy images reveal that Mn-HDCL exists as a 2D sheet-like structure. In Mn-HDCL, the manganese­(IV) ion is trapped within the cavity of the cage-like ligand. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 60 publications
(83 reference statements)
0
15
0
Order By: Relevance
“…Since silica-cored Au nanoshells served as the first photothermal nanomaterials for clinical use, more and more inorganic agents with strong absorption in the NIR region, high chemical stability, adjustable water solubility, and minimal cytotoxicity have entered clinical trials. , Clinical trials have also been underway for small organic molecules due to their good biodegradability, good repeatability, and simple preparation. , Nevertheless, the major challenges for the clinical implementation of photothermal nanomaterials are the complex metabolism and excretion behaviors . The representative works on PTT with diverse photothermal nanomaterials in recent years are summarized in Table .…”
Section: Applicationsmentioning
confidence: 99%
“…Since silica-cored Au nanoshells served as the first photothermal nanomaterials for clinical use, more and more inorganic agents with strong absorption in the NIR region, high chemical stability, adjustable water solubility, and minimal cytotoxicity have entered clinical trials. , Clinical trials have also been underway for small organic molecules due to their good biodegradability, good repeatability, and simple preparation. , Nevertheless, the major challenges for the clinical implementation of photothermal nanomaterials are the complex metabolism and excretion behaviors . The representative works on PTT with diverse photothermal nanomaterials in recent years are summarized in Table .…”
Section: Applicationsmentioning
confidence: 99%
“…A search in the Cambridge Structural Database (CSD version 5.43, update of November 2022; Groom et al, 2016) resulted in nine hits dealing with hydrazide-based clathrochelates of 3dmetals. There are three structures of Mn IV clathrochelates (Shylin et al, 2021;Xu et al, 2022), three structures of Fe IV clathrochelates (Tomyn et al, 2017) and three hits dealing with…”
Section: Database Surveymentioning
confidence: 99%
“…The MOFs reveal a 1D coordination polymer topology: the Fe IV clathrochelate complex anions being connected by Mn 2+ (Xu et al, 2020b) or Cu 2+ (Xu et al, 2020a(Xu et al, , 2022 cations, forming zigzag hetero-bimetallic chains, and being bimetallic helps to understand the link with Mn 2+ and Cu 2+ .…”
Section: Figurementioning
confidence: 99%
“…ii , 178.31 (18)°. The ranges of equatorial cissoid angles [88.8(2)°90.9(2)°] and the values of the transoid angles [178.4(2)° and 179.18 (19)°] reflect the slightly distortion of the N 2 O 4 environment from the ideal octahedral geometry. In each ligand molecule, the phenyl ring of the Schiff base lies in a plane including its phenolate oxygen (rms 0.0805 Å and 0.0212 Å).…”
Section: Structure Of the Polymeric Complexmentioning
confidence: 99%
“…It has been reported that in these enzymes, manganese is involved in complex redox cycles with diverse oxidation states [14][15][16][17]. In coordination chemistry, many complexes in which manganese is found in various environments have shown good redox properties with oxidation states ranging from Mn 2+ to Mn 5+ [18][19][20][21]. These phenomena are very useful for understanding and modeling the functioning of active enzymes.…”
Section: Introductionmentioning
confidence: 99%